The Relationship Between New Media and the Stereotype of Syrian Refugees in the Middle East - Abualasal, Nawzat Saleh; Khasawneh, Belal; Alaawad, Haitham Adelrahman; Ziani, Abdulkrim; Habes, Mohammed (Journal of Posthumanism, 2025)
The current study aims to study the impact of social media on the perceptions of Syrian refugees within Jordanian society. It also sheds light on how stereotypes about refugees are manufactured and promoted through various platforms on the Internet, which leads to the spread of misleading information, biased reports and sensational narratives. The study followed the descriptive quantitative approach in its procedures by relying on the questionnaire as a tool for collecting data from the sample using a random sample approach consisting of (203) individuals from the communities of Mafraq and Irbid cities, selected from students at Al al-Bayt and Yarmouk Universities. The results show: One of the most important mechanisms for shaping the image of the Syrian refugee in social media in Jordanian society is that they are partners in society and have become part of it, and that there are effects of the historical link and tribal extension between the two peoples. The results did not show negative stereotypes towards the Syrian refugee, which may be due to their achievements in various fields, and the return of this is due to their efforts and rapid integration into the societies in which they live. The process of integrating refugees also has many positive repercussions on the host community, including projects that may Contribute to the prosperity of the host country's economy.